Jumlah Bakteri Pseudomonad Fluoresen Isolat Cas dalam Berbagai Formula Media Tumbuh - Devi Aprillia Sary; Linda Advinda (Symbiotic: Journal of Biological Education and Science, 2021)
Fluorescent pseudomonad is a biological agent that can be used as a controlling plant disease, increasing plant growth and phosphate availability for plants, as well as producing compounds that are signals for plants to produce secondary metabolites that are antimicrobial. Pseudomonad fluorescent can be grown in various growing media. The purpose of the study was to find out the number of pseudomonad fluorescent bacteria in Cas isolates grown in various formulas. This research is an experimental study. The design used complete random design (RAL) with 5 treatments and 3 replays. The treatment is formula M1 (molasses 10 g/L+ ZA 5 g/L), M2 (molasses 10 g/L+ ZA 10 g/L), M3 (molasses 5 g/L+ ZA 5 g/L), M4 (molasses 5 g/L+ ZA 10 g/L), and M5 (NB 8 g/). The data obtained was analyzed with Anova and DNMRT dvanced tests at a real rate of 5%. The results showed that pseudomonad fluorescent isolate Cas grown in formula M3 ( molasses 5g/L + ZA 5 g/L) produced the highest number of bacteria which is 118.3 x 108 while the lowest number of bacteria in formula M5 ( NB 8g/L) is 9.76 x 108 cfu/mL.